1999
DOI: 10.1042/0264-6021:3430461
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor-1 interacts with the glucose-regulated protein GRP75/mortalin

Abstract: Fibroblast growth factor-1 (FGF-1), which lacks a signal peptide and is intracellularly localized as a result of endogenous expression or endocytosis, is thought to be involved in regulating cell growth and differentiation. In the study reported here, we purified proteins that bind intracellular FGF-1. Affinity adsorption was used to purify FGF-1-binding proteins from rat L6 cells expressing FGF-1. One of the isolated proteins was identified as the glucose-regulated protein GRP75/mortalin/PBP-74/mthsp70, a mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 33 publications
1
47
0
Order By: Relevance
“…Interestingly, GRP75 has many assigned functions, including intracellular trafficking (26,27). Although the identification of this protein as an NF-SLN-interacting candidate appeared particularly attractive to investigate further, we were unable to verify these findings by conventional IPs.…”
Section: Discussionmentioning
confidence: 38%
“…Interestingly, GRP75 has many assigned functions, including intracellular trafficking (26,27). Although the identification of this protein as an NF-SLN-interacting candidate appeared particularly attractive to investigate further, we were unable to verify these findings by conventional IPs.…”
Section: Discussionmentioning
confidence: 38%
“…Previous studies have suggested that GRP75 (also known as "PBP74") not only is present in the endoplasmic reticulum (ER) but also is associated with the plasma membrane and in early endocytic vesicles in immune cells, suggesting a role in antigen processing (14). Others have reported on cytosolic localization of GRP75 (also known as "mortalin"), where it may regulate the activity of p53 (15) and FGF (16). More recent proteomic analyses of detergent-resistant membrane fractions have suggested GRP75 is a ubiquitously expressed membrane lipid raft protein (17); however, the role of GRP75 in endocytic mechanisms remains unknown.…”
Section: Resultsmentioning
confidence: 99%
“…It is of interest that a third protein in the large heatshock family, mortalin (GRP75, match number 330 and 340) (68), seems to be posttranslationally modified in response to cytokines and the NO inhibitor because the expression levels were changed in opposite directions in the two spots. GRP75 is a glucose-regulated stress-inducible mitochondrial chaperone protein, possibly involved in antigen-processing and cell mortality (68).…”
Section: Discussionmentioning
confidence: 99%